Drosha drives the formation of DNA:RNA hybrids around DNA break sites to facilitate DNA repair - Wei-Ting Lu (Nature Portfolio, 2018)
The mechanism through which Drosha and Dicer affect DNA repair is not clear. Here the authors use a high-throughput approach to uncover the role of Drosha in promoting DNA:RNA hybrids at DNA damaged sites.